KONSEP NARIMA ING PANDUM DALAM PENERIMAAN DIRI LANSIA JAWA - Lintang Seira Putri (Academic Journal of Psychology and Counseling, 2020)
The concept of narima ing pandum is a self-acceptance form of the elderly people in the context of Javanese culture. The purpose of this study was to determine the concept of narima ing pandum in the form of meaning and aspects in Javanese elderly people’s self-acceptance. This qualitative research uses a phenomenological approach by collecting data through focus group discussions and in-depth interviews. The results of this study indicate that self-acceptance in Javanese society is represented in the concept of narimo ing pandum. Narimo ing pandum in the context of Javanese elderly people is a condition of accepting whatever has been given by God, regardless of the condition and regardless of the amount efforts the individual has tried according to his/her ability level. The aspects which make up the concept of narimo ing pandum include gratitude, ora ngoyo/ngongso, and simplicity. Elderly people who has an attitude of self-acceptance or have an attitude of narimo ing pandum will have a sense of calm or ayem in living their life.